Management of Gastroschisis: Results From the NETS2G Study, a Joint British, Irish, and Canadian Prospective Cohort Study of 1268 Infants. Issue 6 (June 2021) - Allin, Benjamin S. R.; Opondo, Charles; Kurinczuk, Jennifer J.; Baird, Rob; Puligandla, P.; Skarsgard, Erik; Knight, Marian
Abstract : Objective: In infants with gastroschisis, outcomes were compared between those where operative reduction and fascial closure were attempted ⩽24 hours of age (PC), and those who underwent planned closure of their defect >24 hours of age following reduction with a pre-formed silo (SR). Summary of Background Data: Inadequate evidence exists to determine how best to treat infants with gastroschisis. Methods: A secondary analysis was conducted of data collected 2006–2008 using the British Association of Pediatric Surgeons Congenital Anomalies Surveillance System, and 2005–2016 using the Canadian Pediatric Surgery Network. 28-day outcomes were compared between infants undergoing PC and SR. Primary outcome was number of gastrointestinal complications. Interactions were investigated between infant characteristics and treatment to determine whether intervention effect varied in sub-groups of infants. Results: Data from 341 British and Irish infants (27%) and 927 Canadian infants (73%) were used. 671 infants (42%) underwent PC and 597 (37%) underwent SR. The effect of SR on outcome varied according to the presence/absence of intestinal perforation, intestinal matting and intestinal necrosis. In infants without these features, SR was associated with fewer gastrointestinal complications [aIRR 0.25 (95% CI 0.09–0.67, P = 0.006)], more operations [aIRR 1.40 (95% CI 1.22–1.60, P < 0.001)], more days PN [aIRR 1.08 (95% CI 1.03–1.13, P < 0.001)], and a higher infection risk [aOR 2.06 (95% CI 1.10–3.87, P = 0.025)]. In infants with these features, SR was associated with a greater number of operations [aIRR 1.30 (95% CI 1.17–1.45, P < 0.001)], and more days PN [aIRR 1.06 (95% CI 1.02–1.10, P = 0.003)]. Conclusions: In infants without intestinal perforation, matting, or necrosis, the benefits of SR outweigh its drawbacks. In infants with these features, the opposite is true. Treatment choice should be based upon these features. Abstract : Supplemental Digital Content is available in the text